Does Intellectual Capital Can Moderated Sharia Compliance Performance on Financial Performance? - Noer Sasongko; Triyono; Kartika Toyibi (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: With intellectual capital acting as a moderator, this study will examine how financial success is impacted by sharia compliance performance as measured by the Maqashid Syariah Index, Profit Sharing Ratio, Zakat success Ratio, and Islamic Income. Methodology/approach: This study uses panel data techniques with MRA testing and using the Eviews 12 Program. Findings: The study's findings show that the main factor influencing financial performance is the profit sharing ratio; the Maqashid Shariah Index, profit sharing ratio, zakat performance ratio, and Islamic income variables cannot be moderated by the intellectual capital variable. Practical implications: This study provides a new contribution in the field of accounting related to the performance of sharia banking compliance in Indonesia, and is a consideration for companies and stakeholders in making decisions in order to maximize financial performance. Originality/value: This study adds the Maqashid Shariah Index variable in measuring the performance of sharia banking compliance in Indonesia.